CHALLENGES IN TRANSLATING GERMAN AND ENGLISH IDIOMS INTO UZBEK: A COMPARATIVE ANALYSIS - Yusufjonova Shaxloxon Muxtorovna (Bright Mind Publishing, 2025)
Translating idioms from German and English into Uzbek presents unique challenges due to cultural, linguistic, and semantic differences. This article explores the complexities involved in such translations, highlighting the importance of cultural context, semantic equivalence, and the translator's role in preserving meaning and nuance. Through comparative analysis, the study underscores the necessity for adaptive strategies to achieve accurate and culturally resonant translations.
Keywords: Idioms, translation, German, English, Uzbek, cultural context, semantic equivalence.